Preimplantation genetic testing for recurrent autosomal dominant osteogenesis imperfecta associated with paternal gonosomal mosaicism - Bai, Haiyan; Li, Xiaofang; Liu, Xitong; Shi, Wenhao; He, Bin; Wei, Ruiyang; Shi, Juanzi (Frontiers in Genetics, 2022)
Research Question: How to prevent the transfer of a mutation causing osteogenesis imperfecta (OI) to offspring in a couple with recurrent adverse pregnancy outcomes, when the male partner is a gonosomal mosaic carrier. Design: High-throughput sequencing and first-generation DNA sequencing were performed using the tissues from an aborted foetus and its parents. Regions 2 Mb upstream and downstream of the COL1A1 gene were subjected to multiplex PCR to identify single nucleotide polymorphisms (SNPs) and family haplotypes associated with the disease-causing mutation. Single-cell whole-genome amplification and sequencing were performed on trophoblasts cultured in vitro for 5–6d to construct embryonic SNP haplotypes, and first-generation sequencing was used for pathogenic locus verification and aneuploidy screening. Preimplantation genetic testing for monogenic disorders (PGT-M) was also performed. Results: The aborted foetus was heterozygous for the COL1A1 mutation c.1454G>A (chr17-48272089, p.Gly485Asp) suspected to cause OI. The variant was also detected in the peripheral blood cells and sperm of the male partner, who appeared to be a gonosomal mosaic carrier of the mutation. Three morphologically usable blastocysts were obtained in vitro and successfully expanded after a trophectoderm biopsy. Two blastocysts were unusable owing to aneuploidy; however, one was euploid and did not carry the paternal mutation. Post-transfer gestation was confirmed by systematic B-scan ultrasound, and amniocentesis findings were consistent with the PGT-M results. Conclusions: Parental gonadal mosaicism was the cause of recurrent terminated pregnancies due to foetal skeletal dysplasia. Using PGT-M to select embryos without the paternal pathogenic mutation prevented the vertical transmission of OI in this family, and a successful pregnancy was achieved.